2019
DOI: 10.1111/neup.12564
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity of myelin‐associated oligodendrocytic basic protein in Lewy bodies

Abstract: Myelin‐associated oligodendrocytic basic protein (MOBP) plays a role in structural maintenance of the myelin sheath in the central nervous system. Recent genome analyses have revealed that mutation in MOBP is a risk factor for various neurodegenerative diseases, including Alzheimer's disease (AD), tauopathies and transactivation response DNA‐binding protein 43 kDa proteinopathies. Proteomics analysis has shown that MOBP is a component of cortical Lewy bodies (LBs). However, the immunohistochemical localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
9
1
1
Order By: Relevance
“…Furthermore, we found strong immunopositive staining for MOBP in MSA cerebellar GCIs but not in midbrain PD Lewy bodies, nor in frontal cortex PSP or HD inclusions. Our findings contrast with results from a recent study by Kon et al, 47 who reported negative immunoreactivity for MOBP in cerebellar MSA GCIs, but positive immunoreactivity for MOBP in a proportion of Lewy bodies in PD and dementia with Lewy bodies cases. Technical differences between these two studies may contribute to the observed discrepancy in the immunostaining.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we found strong immunopositive staining for MOBP in MSA cerebellar GCIs but not in midbrain PD Lewy bodies, nor in frontal cortex PSP or HD inclusions. Our findings contrast with results from a recent study by Kon et al, 47 who reported negative immunoreactivity for MOBP in cerebellar MSA GCIs, but positive immunoreactivity for MOBP in a proportion of Lewy bodies in PD and dementia with Lewy bodies cases. Technical differences between these two studies may contribute to the observed discrepancy in the immunostaining.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, patients with multiple system atrophy, a disease with a known α‐synuclein pathology, did not test positive for MOBP, and as such, MOBP seems to act independently of α‐synuclein. Regarding cortical LBs, the researchers also reported a small amount of MOBP 35 . Given that MOBP has been reported elevated in neurotoxic conditions in test subjects, 36 and that it does not seem to contribute to α‐synuclein aggregation, it is possible that its elevation reflects a compensatory mechanism that ultimately fails to protect the cells from degenerating.…”
Section: Discussionmentioning
confidence: 98%
“…The association of MOBP with other neurodegenerative diseases is well-established. To date, autoreactivity against MOBP has been detected among individuals with MS [13,15] and MOBP immunoreactivity has been detected in the core of Lewy Bodies (LBs) among patients with Parkinson' s disease and dementia with LBs [37,38]. MOBP SNPs have been associated with Apolipoprotein-E e4 positive AD [14], FTD (and the severity of white matter degeneration [16,39]), PSP [17,[40][41][42][43][44], Corticobasal Degeneration [43,44], while decreased expression of MOBP was revealed in familial Globular Glial Tauopathy [45] and differential DNA methylation of MOBP was shown in Multiple System Atrophy [46].…”
Section: Discussionmentioning
confidence: 99%